THE SENTENCE ANALYSIS TO THE EACH VERSE OF QUR’AN SUROH AL-IKHLAS, AL-FALAQ, AN-NAS - YUSNI SINAGA (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract : The all samawi religions can be said as the international religion because the followers of each religion can be found in most of countries in the world. So, islamy is one of the international religion that should be studied by the islam followers especially and all human in this world generally. Especially to the islam followers, they must study the alquran well so that they can make the alquran as their way or view of life means the alquran is their indicator for them in taking judgement in their life. Cause of the followers separated in all countries or can be found in most of countries so the alquran needed to be translated in all language in the world. No exception in English translation. That is why the alquran must be analyzed scientific in all business especially in education such as in linguist. Keywords: Analyze, Sentence, Al-Qur’an